Pengembangan Kualitas Layanan ”Solusi Duka Indonesia” dengan Metode Design Thinking - Catherine Erica Bing; Felecia Felecia (Jurnal Titra, 2022)
PT. Solusi Duka Indonesia, which was established in 2018, have helped many people with their service to accompany the moment of grief. PT. Solusi Duka Indonesia innovates to provide mourning services because of their emphaty for people who feel lost and then hindered by space and time to attend mourning events. Currently the sales target is not enough, for that it is necessary to improve the quality of service. The goal is that more of them use the Solusi Duka Indonesia so that the company can survive. The method used in this research is design thinking. Design thinking is a creative process that focused on human needs and provides impetus for creating creative solutions. In this method there are activities to interview respondents and conduct surveys to respondents who have experienced grief. Based on the result of the research that has been carried out, several problems were found that can be used as suggestions for developing the quality of service for the Solusi Duka Indonesia. One of the result of the proposal given is the addition of a death file management feature as many as 31 respondents chose.